Research Trends in Digital Media Development for Mathematics Subjects in Primary Schools Between 2015-2025 - Yulianti, Leni; Trimurtini, Trimurtini; Subali, Bambang; Ellianawati, Ellianawati (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to identify trends in digital media development in mathematics learning in elementary schools during the period 2015-2025. The method employed is a systematic review using the PRISMA approach, which involves 25 selected articles from relevant national and international journals. Article selection is based on specific inclusion and exclusion criteria. A bibliometric analysis was conducted using VOSviewer software to map the relationships between keywords, authors, and topics. The results of the analysis indicate an increase in research trends over the last decade, with a primary focus on interactive digital media, including Android applications, educational games, and augmented reality. The dominant keywords that emerge are digital media, mathematics, and elementary schools, which are often associated with increased motivation and student learning outcomes. Visualization from VOSviewer reveals the main clusters that connect learning technology, media effectiveness, and curriculum innovation. These findings provide a comprehensive overview of the direction of digital media development in elementary mathematics education. They can serve as an important reference for researchers and practitioners in developing innovative and relevant learning strategies to meet the needs of the 21st century.